Effect of dexamethasone chronic administration on the hepatic sulphoxidation of albendazole in sheep - Virkel, Guillermo Leon (2009)
Albendazole (ABZ), a broad spectrum antiparasitic drug, is oxidized into albendazole sulphoxide (ABZSO) by both flavin-containing monooxygenase (FMO) and cytochrome P450 (CYP). Changes on the metabolic activities of both enzyme systems may affect the persistence of these anthelmintic molecules in target tissues. We hypothesized that chronic administration of the CYP3A inducer dexamethasone (DEX) increases the CYP-mediated metabolism of ABZ in sheep liver. The enantioselective sulphoxidation of ABZ was evaluated in hepatic microsomes obtained from untreated and DEXtreated sheep (7 days at 3 mg/kg/day). CYP3A-mediated erythromycin and triacetyl-oleandomycin Ndemethylations were, respectively, 3.6- and 2.7-fold higher (P<0.05) in liver microsomes obtained from DEXtreated sheep. However, the hepatic CYP-mediated sulphoxidation of ABZ was not affected by DEX chronic administration. On the other hand, the FMO-dependent activity (methimazole S-oxidation) was 28 % lower in liver microsomes from DEX-treated sheep, which correlated with a lower FMO-mediated enantioselective sulphoxidation of ABZ. In conclusion, the CYP3A subfamily is not involved in ABZ hepatic sulphoxidation. Moreover, chronic administration of DEX in sheep may have detrimental effects on the FMO-mediated metabolism. This may affect the disposition of ABZ and its active metabolite in target tissues of parasite location.